Atelocollagen-Embedded Chondrocyte Precursors as a Treatment for Grade-4 Cartilage Defects of the Femoral Condyle: A Case Series with up to 9-Year Follow-Up - Hwa-Chang Liu; Tzu-Shang Thomas Liu; Yen-Liang Liu; Jyh-Horng Wang; Chih-Hung Chang; Tiffany Ting-Fang Shih; Feng-Huei Lin (Biomolecules, 2021)
We demonstrated the safety and efficacy of autologous chondrocyte precursor (CP) cell therapy in repairing Grade 4 cartilage defects of medial femoral condyles. The autologous bone marrow mesenchymal stem cells of each participant were isolated, amplified, and then differentiated into CPs in atelocollagen. Neotissues made of CPs were implanted into cartilage defects with an average cell density of 4.9 ± 2.1 × 106 cells/cm2 through arthrotomy. The knee function was evaluated with the International Knee Documentation Committee (IKDC) subjective knee form. Patients’ knee functions significantly improved by the 28th week (IKDC score = 68.3 ± 12.1), relative to the initial functionality before the CP therapy (IKDC score = 46.1 ± 16.4, p-value = 0.0014). Nine of these twelve patients maintained good knee functions for 9 years post-implantation (IKDC score = 69.8 ± 12.3) at levels higher than the pre-implantation values (p-value = 0.0018). Patients were evaluated with MRI and arthroscopy, and the defective sites exhibited a smooth surface without a gap between the implant and host tissue. This study demonstrates that autologous CPs successfully engraft into the host tissue and result in the re-formation of hyaline-like cartilage, thereby improving the impaired knee functions. Most importantly, no adverse event was reported during this long-term follow-up period.